A Qualitative Study on Millennials Consumption Behavior of Alcohol Beverages in Jakarta, Indonesia - Konco Martalegawa; Betsy Vevyola Prihatini Gultom; Faradi Pramudito; Muhammad Badri Halim; Rizal Taufik (Universitas Prasetiya Mulya, 2022)
Without a doubt, millennials play an important role in the industry as the power horse of future consumers. Although they are financially struggled compared to other generations, they are known to be a highest spender compared to other generations, and their buying preference has the power to make or break industries. This research aims to explore the alcohol consumption of Indonesian millenials ages 21-24-year-old in Jakarta region, Indonesia. The study also investigates factors that determine the consumption behavior. A qualitative method using 24 in-depth interviews was applied to address the research questions. The research findings indicate that the millennial’s alcohol consumption behavior is not only determined by functional and social factors, but also emotional factor, and that they tended to consume alcohol drink both spontaneously and purposively.